VEGF-C level as a predictor of pelvic lymph node metastases of cervical cancer at early stage (Faculty of Medicine Universitas Indonesia, 2009)
Aim Vascular endothelial growth factor (VEGF) works to stimulate angiogenesis and lymphogenesis which is one of the factors in the metastasis process. This study aimed to identify whether VEGF level could be used to predict metastasis into pelvic lymph node of stage IB-IIA cervical cancer. Methods The study was case control study, a case (cervical cancer metastasis into pelvic lymph node), a control (cervical cancer without metastasis). Independent variables included primary lesion size, histological type, grade of cell differentiation, lymph vascular space involvement, and VEGF level. Dependent variable was metastasis into pelvic lymph node. Results Based on cut-off point, VEGF-C serum level, i.e., 10,066.90 pg/ml, 11/47 patients or 23.41%, had the level above that value, and 10/11 of the group of patient or 90.91% were found to develop metastasis into pelvic lymph node. Sensitivity of the examination of VEGF-C level in relation to the risk for the incidence of lymph node in this study was 71.43%, with a specificity of 96.97%, positive predictive value (PPV) of 90.91%, and negative predictive value (NPV) of 88.89%. Conclusion: VEGF-C level in the serum could be used to predict lymph node metastasis of stage IB-IIA cervical cancer, with a sensitivity of 71.43% and specificity of 96.97%. (Med J Indones 2009; 18: 257-61)